An efficient and broadly applicable method for transient transformation of plants using vertically aligned carbon nanofiber arrays - Morgan, Jessica M.; Jelenska, Joanna; Hensley, Dale; Retterer, Scott T.; Morrell-Falvey, Jennifer L.; Standaert, Robert F.; Greenberg, Jean T. (Frontiers in Plant Science, 2022)
Transient transformation in plants is a useful process for evaluating gene function. However, there is a scarcity of minimally perturbing methods for gene delivery that can be used on multiple organs, plant species, and non-excised tissues. We pioneered and demonstrated the use of vertically aligned carbon nanofiber (VACNF) arrays to efficiently perform transient transformation of different tissues with DNA constructs in multiple plant species. The VACNFs permeabilize plant tissue transiently to allow molecules into cells without causing a detectable stress response. We successfully delivered DNA into leaves, roots and fruit of five plant species (Arabidopsis, poplar, lettuce, Nicotiana benthamiana, and tomato) and confirmed accumulation of the encoded fluorescent proteins by confocal microscopy. Using this system, it is possible to transiently transform plant cells with both small and large plasmids. The method is successful for species recalcitrant to Agrobacterium-mediated transformation. VACNFs provide simple, reliable means of DNA delivery into a variety of plant organs and species.